Lepidoptera, associated with Eucalyptus plantations, captured with light traps in Aracruz and São Mateus, Espírito Santo State, Brazil - Zanuncio, Jose; Santos, Germi; Zanuncio, Teresinha; Laranjeiro, Alberto (Bosque (Valdivia), 1998)
Insects were collected in two Eucalyptus plantations, one in Aracruz and the other in São Mateus, Espírito Santo State, Brazil, using two light traps once every fifteen days from November 1989 to October 1990. The insects captured were sent to the Forest Entomology Laboratory, at the Federal University of Viçosa, in Viçosa, Minas Gerais State, Brazil. A total of 62 species of Lepidoptera were identified for the two regions. They were divided by groups, into primary and secondary pests of Eucalyptus (other identified and non identified species). In Aracruz, 12 and 10 species were considered primary and secondary pests of Eucalyptus, respectivelly. In São Mateus, 10 and 9 species. Main primary pests captured were Eupseudosoma aberrans (Arctiidae) and Stenalcidia sp. (Geometridae) while Idalus affinis (Arctiidae) and Nystalea nyseus (Notodontidae) were the largest groups of secondary pests of Eucalyptus.